High Purity Orbital Angular Momentum Modes Reconfiguration Using Uniform Circular Array Antenna to Enhance Channel Capacity and Spectral Efficiency - ., RAKHEE; Bhadada, Rajesh; ., Usha (International Journal of Experimental Research and Review, 2023)
Technology based on OAM (orbital angular momentum) has great potential for enhancing the bandwidth efficiency of telecommunication systems. Although OAM waves are orthogonal, it is possible to multiplex various modes within a single frequency channel. Significantly, the overall spectrum efficiency, as well as channel capacity, can be improved. Multiple users can share the same frequency channel by using orthogonal modes, which eliminates the requirement for extra resources like time and frequency. This research uses MATLAB code to derive a uniform circular array (UCA) antenna factor under the cylindrical coordinate system. This factor is used to illustrate the array antenna's electric field to generate OAM waves or radio waves that carry the OAM mode. OAM modes can be reconfigured for the no. of UCA elements (N) needed to generate a ripple-free radiation pattern based on the UCA antenna factor. Additionally, the significance of UCA radius and observational distance (the field plane-UCA plane gap) on the phase distribution and radiation pattern from OAM mode 1 to 5 is graphically evaluated and optimized. The MATLAB simulations compute the electric field phase distribution pattern (EFPDP) and normalized radiation pattern (NRP) at 76 GHz. The method predicts the peak, side lobes, and comparable radiation patterns of the radiation pattern, offering an effective means of optimizing OAM modes and analysing trade-offs.